Preliminary Study of Human Performance and Neuroscience in Indonesia - Suzy Yusna Dewi; Taufiq Fredrik Pasiak; Rizki Pauziah Hapit; Yasmin Azizah Idhsa; Muthia Rahmah; Djakiyah Kalsum Amzi; Herdan Listianto (Tazkiya Journal of Psychology, 2025)
Effective work performance is driven by motivation, emotional regulation, and the ability to build social relationships, which collectively influence professional outcomes. Quantitative electroencephalography (qEEG) offers an objective measure of brain activity related to these factors, providing insights into the neural mechanisms underlying workplace behavior.  This study is an exploratory pilot investigation of associations between quantitative EEG (qEEG) parameters at left DLPFC (Fp1) and workplace-relevant functions (emotional regulation, motivation, social relations) assessed with selected MMPI-180 subscales. Brain activity was recorded at the left dorsolateral prefrontal cortex (Fp1), focusing on Theta, Alpha, and Beta power. Data were collected from 68 employees in Indonesia over two months and analyzed using linear regression in SPSS 23. Results showed that Beta power at Fp1 significantly predicted emotional regulation (B = 6.85, p = .04, R² = 6.4%), Alpha power at Fp1 predicted motivation (B = 6.02, p = .048, R² = 5.8%), and Theta power at Fp1 predicted social relationship skills (B = 14.15, p = .006, R² = 16.3%). These findings provide empirical evidence that specific brainwave activities are linked to different aspects of workplace performance. The contribution of this study lies in demonstrating the applicability of qEEG as an objective tool to evaluate employee performance, offering new insights for neuroscience-based organizational interventions in the Indonesian context.